2020
DOI: 10.1007/s42995-020-00053-z
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for culturing active/dormant marine microbes

Abstract: Microorganisms are ubiquitous in the ocean environment and they play key roles in marine ecosystem function and service. However, many of their functions and phenotypes remain unknown because indigenous marine bacteria are mostly difficult to culture. Although many novel techniques have brought previously uncultured microbes into laboratory culture, there are still many most-wanted or key players that need to be cultured from marine environments. This review discusses possible reasons for 'unculturable microbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 86 publications
1
28
0
Order By: Relevance
“…If VBNC cells are unable to go into the lag phase in an appropriate time period (Fig. 1), they may well maintain dormancy or even lose viability on the media (Mu et al ., 2021; Zhang et al ., 2021). This is a major difference between VBNC and persister cells, which pertains to resuscitation dynamics.…”
Section: Resuscitation Of Vbnc Cellsmentioning
confidence: 99%
“…If VBNC cells are unable to go into the lag phase in an appropriate time period (Fig. 1), they may well maintain dormancy or even lose viability on the media (Mu et al ., 2021; Zhang et al ., 2021). This is a major difference between VBNC and persister cells, which pertains to resuscitation dynamics.…”
Section: Resuscitation Of Vbnc Cellsmentioning
confidence: 99%
“…Further results showed that marine Gaiellales strains were hygrophilous and halophilic, different from the species G. occulta. Therefore, simulating the natural environment, especially its potential key factors, is an effective strategy for isolating novel, rare, or uncultured bacteria (Mu et al, 2020).…”
Section: Isolation Strategies For Rubrobacterales and Gaiellalesmentioning
confidence: 99%
“…However, these antifungal compounds have not always proven to be effective and fungicides like pevaryl (econazole nitrate; 1%) and benlate (benomyl, or methyl l-(butylcarbamoyl)-2-benzimidazole carbamate;4 mg•ml −1 ) appear to be more adequate in inhibiting fungal growth (Lage and Bondoso, 2011). Futhermore, when the targated strains belong from marine sample, the authors commonly use filtired marine water or artificial seawater in order to complement the medium and to reach the bacterial natural environment (Schlesner, 1994;Mu et al, 2020;Wiegand et al, 2020). This was especially relevant for marine aquatic Planctomycetes.…”
Section: Gaps In the Current Media For Planctomycetes Isolationmentioning
confidence: 99%